California Bowl Football Game at Bulldog Stadium; Eastern Michigan Hurons 30 v. San Jose Spartans 27 - Watkins, Howard::::::::: (1987)
Blues jazz band playing at East Fresno Rotary tailgate; tuba, trombone, trumpet, banjo and drummer